2004
DOI: 10.3748/wjg.v10.i22.3269
|View full text |Cite
|
Sign up to set email alerts
|

Capsule oxymatrine in treatment of hepatic fibrosis due to chronic viral hepatitis: A randomized, double blind, placebo-controlled, multicenter clinical study

Abstract: Oxymatrine capsule is effective and safe in treatment of hepatic fibrosis due to chronic viral hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Hepatic fibrosis is a known cause of several regional hepatic hemodynamics changes including the hepatic blood flow, resistive index, and the portal vein velocity. 4 In cirrhosis, portal blood inflow, hepatic resistance and portal venous pressure increases. Despite the initial increase, portal blood inflow decreases with increasing sinusoidal resistance and development of portosystemic collateral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis is a known cause of several regional hepatic hemodynamics changes including the hepatic blood flow, resistive index, and the portal vein velocity. 4 In cirrhosis, portal blood inflow, hepatic resistance and portal venous pressure increases. Despite the initial increase, portal blood inflow decreases with increasing sinusoidal resistance and development of portosystemic collateral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several multicenter RCTs have confirmed that TCM can reverse liver fibrosis [49][50][51] . FZHYC was used to treat liver fibrosis in patients with CHB for six months.…”
Section: Chinese Materia Medica Is Frequently Used To Treat Liver Dismentioning
confidence: 87%
“…Immune-stimulative activity that changes the immune response of HBV-transgenic mice from a Th2 (IL-4 and IL-10) to a Th1 (IFN-γ and IL-2) response has been also reported (Dong et al, 2002;Yang et al, 2002). Because these animal studies and cell-based experiments showed promising effects against HCV infection, several clinical studies have been conducted (Li et al, 1998;Mao et al, 2004). A review paper has evaluated the efficacy of several natural products reported in the treatment of chronic HCV subjects.…”
Section: Oxymatrinementioning
confidence: 99%